2022
DOI: 10.1039/d2dt01409b
|View full text |Cite
|
Sign up to set email alerts
|

Solubility of Ca(ii), Ni(ii), Nd(iii) and Pu(iv) in the presence of proxy ligands for the degradation of polyacrylonitrile in cementitious systems

Abstract: The solubility of Ca(OH)2(cr), β-Ni(OH)2(cr), Nd(OH)3(s) and PuO2(ncr, hyd) was investigated in cement porewater solutions containing glutarate (GTA), a-hydroxyisobutarate (HIBA) and 3-hydroxybutarate (HBA). These ligands were proposed as probable degradation...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 69 publications
(145 reference statements)
4
8
0
Order By: Relevance
“…1 This concentration is in line with previous data reported in the literature (Ochs et al, 2016) but higher than the solubility limit of β-Ni(OH) 2 (cr) determined under analogous boundary conditions (González-Siso et al, 2018;Szabo et al, 2022b). This observation suggests that this solid phase is neither present in the cement not forming within the timeframe of our experiments.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…1 This concentration is in line with previous data reported in the literature (Ochs et al, 2016) but higher than the solubility limit of β-Ni(OH) 2 (cr) determined under analogous boundary conditions (González-Siso et al, 2018;Szabo et al, 2022b). This observation suggests that this solid phase is neither present in the cement not forming within the timeframe of our experiments.…”
Section: Resultssupporting
confidence: 92%
“…The results obtained for the sorption of these radionuclides in the presence of proxy ligands are compared with analogous studies in the presence of ISA, which shares some structural similarities with HIBA and HBA. The present work complements and further expands the experimental studies by Szabo et al dedicated to the proxy ligands of UP2W, i.e., evaluating their effect on the solubility of selected radionuclides (Szabo et al, 2022b) and assessing their uptake by HCP (Szabo et al, 2022a). Frontiers in Nuclear Engineering frontiersin.org in a previous study (Altmaier et al, 2008).…”
Section: Introductionsupporting
confidence: 63%
See 1 more Smart Citation
“…No thermodynamic studies are available in the literature dealing with the complexation of HIBA and HBA with Ca in hyperalkaline pH conditions. However, our previous undersaturation solubility experiments with Ca(OH) 2 (cr) in the presence of HIBA and HBA at 10 −6 M ≤ [L] tot ≤ 0.1 M confirmed that CaL complexes involving the deprotonation of the alcohol group are either very weak or not forming at all (Szabo et al, 2022).…”
Section: Comparison With Sorption Data Available In the Literaturementioning
confidence: 90%
“…The impact of the UP2W degradation products on the solubility and sorption of radionuclides in cementitious systems has been previously investigated in a number of experimental studies (Dario et al, 2004;Holgersson et al, 2011;Duro et al, 2012;Szabo et al, 2022). However, no information is available so far on the interaction of these degradation products with hardened cement paste (HCP), and their possible impact on the surface properties of the latter material.…”
Section: Introductionmentioning
confidence: 99%